Does the Intradiscal Injection of Platelet Rich Plasma Have Any Beneficial Role in the Management of Lumbar Disc Disease?. Issue 3 (April 2022) - Muthu, Sathish; Jeyaraman, Madhan; Chellamuthu, Girinivasan; Jeyaraman, Naveen; Jain, Rashmi; Khanna, Manish
Study Design: Systematic review and meta-analysis. Objectives: We performed this meta-analysis to evaluate whether intradiscal Platelet Rich Plasma(PRP) injection has any beneficial role in the management of lumbar disc disease. Methods: We conducted independent and duplicate electronic database searches including PubMed, Embase, and Cochrane Library till September 2020 for studies investigating the role of intradiscal PRP in the management of lumbar disc disease. The analysis was performed in the R platform using OpenMeta[Analyst] software. Results: 13 studies including 2 RCTs, 5 prospective, and 6 retrospective studies involving 319 patients were included in the meta-analysis. A single-arm meta-analysis of the included studies showed a beneficial effect of the intervention in terms of pain relief outcomes like VAS score (p < 0.001), pain component of SF-36 (p = 0.003) while such improvement was not seen in functional outcome measures like ODI score (p = 0.071), the physical component of SF-36 (p = 0.130) with significant heterogeneity noted among the included studies. No structural improvement in magnetic resonance imaging was observed (p = 0.106). No additional procedure-related adverse events were noted in the included studies (p = 0.662). Conclusion: There is a paucity of high-quality studies to give conclusive evidence on the benefits of intradiscal PRP for lumbar disc disease. Although intradiscal PRP injection has shown some beneficial effect in controlling pain for lumbar disc disease, we could not find structural or functional improvement from the included studies. Hence, we recommend large double-blind double-arm randomized controlled studies to analyze the benefits of the intervention being analyzed.